Conference Room Reverberation Time Correction Using Helmholtz Resonators Lined with Absorbers - Hossein Namvar Arefi; Seyyed Mohammad Amin Ghiasi; Seyyede Mahshid Ghaffari; Farhad Ramezanghorbani; Shiva Sharifpour; Peyman Irajizad; Seyede Delaram Ghoreishi Langroudi; Ahmad Amjadi (Shock and Vibration)
Echo and sound resonance in a conference room cause obscure speech and make listeners tired. Thus, the acoustical properties of a conference room are vitally important. The conference room 412 at Sharif University Physics Department failed to meet basic acoustical standards. The aim of this research is to improve reverberation time (RT) of the conference room using Helmholtz resonators with defined dimensions, diffusers, and sound absorbers. Helmholtz resonators are widely used to absorb sound noise especially at low frequencies. They are particularly useful when noise has a narrow-frequency band. One of the advantages of using Helmholtz resonators is their capacity to be tuned on different frequencies. We enhanced acoustical properties of Helmholtz resonators using proper absorbers and diffusers. In order to decrease the RT, a large number of Helmholtz resonators have been made and installed in proper positions in the conference room. The RT was measured before and after installation. The measurements indicate that the acoustical characteristics of the conference room have been significantly improved.